2008
DOI: 10.1080/15332640802055616
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Drug-Abusing Women With Children in Residential Treatment: A Preliminary Evaluation of Program Retention and Treatment Completion

Abstract: An ex post facto study was conducted to investigate treatment outcomes for 80 women and 168 children admitted into a residential substance-abuse treatment program. The results indicated childhood emotional neglect is a barrier for remaining in and completing treatment for African-American women with comorbid psychological disorders but not for those with crack cocaine dependent disorders. African-American women with comorbid psychological disorders were also three times more likely to dropout of treatment. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 24 publications
(25 reference statements)
0
27
0
Order By: Relevance
“…MOUD use at the time of conception was associated with a longer length of treatment for pregnant women 11 . Involvement with the CJ system and external pressure 36,37 were factors that increased treatment retention. Likewise, having custody of their children increased the likelihood of treatment retention 38 .…”
Section: Resultsmentioning
confidence: 99%
“…MOUD use at the time of conception was associated with a longer length of treatment for pregnant women 11 . Involvement with the CJ system and external pressure 36,37 were factors that increased treatment retention. Likewise, having custody of their children increased the likelihood of treatment retention 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Slightly less than half of all participants were drug-free post 90-days after completing inpatient as indicated by the patient recovery index. It is plausible that participants who were drug-free are the same participants who engaged in formal treatment longer, consistent with retention studies that found the longer length of stay in residential and outpatient is related to higher rates of program completion and better treatment outcomes [26,42].…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, family conflict and low family support contribute to drug use and poor treatment outcomes [20,22,23]. Family conflict has been identified as a strong predictor for initial and continued drug use [24][25][26]. Appel and colleagues et al [27] similarly found that family conflict was a barrier for entering treatment among injection drug users.…”
mentioning
confidence: 96%
“…Sample sizes ranged from 34 30 to 3,482 26 . Sample populations included pregnant and parenting women, 26 , 28 , 29 , 31 , 32 , 41 , 42 adults, 30 , 34 , 38 , 39 , 43 parents involved in the child welfare system, 27 incarcerated individuals, 40 and veterans 33 . Two studies 34 , 43 examined the same sample of adult clients entering two nonprofit inpatient SUD treatment facilities; however, the first study 43 evaluated all incoming clients within an eight-month period, whereas the second evaluated only clients who provided information related to whether they had experienced CSA 34 …”
Section: Resultsmentioning
confidence: 99%
“…Among the 15 reviewed studies, there was substantial heterogeneity among the assessment methods used to evaluate sexual victimization. Although the majority of included studies assessed for lifetime occurrence of sexual victimization, five focused exclusively on childhood sexual victimization 31 , 33 , 34 , 38 , 41 . Additionally, only six 29 32 , 41 , 42 used standardized measures to assess for this history.…”
Section: Resultsmentioning
confidence: 99%